2016
DOI: 10.1002/jip.1462
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of male rape and sexual assault in a male sample from the United Kingdom: Barriers to reporting and the impacts of victimization

Abstract: The present study explored the prevalence of myths about male sexual assault, assault by penetration, and rape in a male general population sample (N = 98; mean age = 26.17 years), with the aim of determining potential barriers to the reporting of incidents of male sexual victimization and reasons for reluctance to report. In addition, the impacts of prior experience of male sexual victimization, both direct and indirect, on rape and sexual assault myth acceptance and on attitudes to reporting were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…[24] Research in the UK found that males were more likely to report sexual assault when another male was the perpetrator compared with a female. [25] Future research should explore differential reporting by male rape victims.…”
Section: Researchmentioning
confidence: 99%
“…[24] Research in the UK found that males were more likely to report sexual assault when another male was the perpetrator compared with a female. [25] Future research should explore differential reporting by male rape victims.…”
Section: Researchmentioning
confidence: 99%
“…The same reasons were given for male victims of sexual assaults, i.e. embarrassment and social stigma, as well as fear of not being believed [4]. However, lack of information on sexual assault on men and lack of an appropriate support system were also cited as reasons for under-reporting by male victims.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, lack of information on sexual assault on men and lack of an appropriate support system were also cited as reasons for under-reporting by male victims. A study published in 2016 and based on 98 male respondents (19 to 58 years old) to an online survey showed that even though they disagreed with the majority of sexual assault/penetration/rape myths, they still believed that men can defend themselves from sexual assault and that the police will not take it seriously if a woman sexually assaults a man [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Statistics show that rape cases are characterized by high attrition rates, which are greatest at the investigative stage ( Parratt and Pina, 2017 ; Sleath and Bull, 2017 ). Moreover, rape victims who approached the police have reported low levels of satisfaction, feelings of not being taken seriously and being poorly or negatively treated ( Jordan, 2001 , 2004 ; Hammond et al, 2017 ). This further raises concern as to a possible impact of officer perceptions and judgments.…”
Section: Introductionmentioning
confidence: 99%